Anagyrus pseudococci Girault (Insecta: Hymenoptera: Encyrtidae) - Theresa Chormanski; Ronald D. Cave (EDIS)
Anagyrus pseudococci is an economically important biological control agent commonly used against the vine mealybug (which infests wine grapes) and the citrus mealybug. It is a solitary, internal parasitoid and lays one egg per host, with the larva developing inside the host’s body. The wasps may be commercially reared and distributed inside mummies, and they will emerge within 1-5 days after delivery. Application involves placing a bottle containing the mummies in a dry spot of the crop and allowing the adults to emerge. This 5-page fact sheet was written by Theresa Chormanski and Ronald D. Cave, and published by the UF Department of Entomology and Nematology, March 2015. (Photo: Kent M. Dane)